2016
DOI: 10.1016/j.jand.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dietary Patterns Derived among the Adult Participants of the National Health and Nutrition Examination Survey 1999-2004 Are Associated with Diet Quality

Abstract: Background Temporal dietary patterns, the distribution of energy or nutrient intakes observed over a period of time, is an emerging area of dietary patterns research that incorporates time of dietary intake with frequency and amount of intake to determine population clusters that may have similar characteristics or outcomes related to diet quality. Objective This study examined whether differences in diet quality were present between clusters of individuals with similar daily temporal dietary patterns. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 36 publications
(53 reference statements)
4
65
1
Order By: Relevance
“…To our knowledge, this is one of the first studies among adults to examine associations for daily temporal eating patterns with energy-adjusted nutrient intakes, diet quality, and adiposity (17). A "grazing" pattern, identified by using LCA and characterized by more frequent EOs found in our earlier study (18), was associated with lower diet quality and higher intakes of discretionary foods in both men and women.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…To our knowledge, this is one of the first studies among adults to examine associations for daily temporal eating patterns with energy-adjusted nutrient intakes, diet quality, and adiposity (17). A "grazing" pattern, identified by using LCA and characterized by more frequent EOs found in our earlier study (18), was associated with lower diet quality and higher intakes of discretionary foods in both men and women.…”
Section: Discussionmentioning
confidence: 71%
“…Studies that examine the temporal patterning of EOs across the day are rare (17). Two studies found distinct temporal eating patterns across the day when applying a data-driven analytic approach, including cluster analysis (17) and latent class analysis (LCA) (18).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations